Penerapan Kurikulum Inovatif Dalam Mewujudkan Kompetensi Berkarakter Di Era Digital - La Ode Fahasini; Elvy Adelina; Findy Feronika; Wika Yolanda; Sahara Sahara (Jurnal Sultra Elementary School, 2024)
The lack of character education for children causes moral crises, such as social problems in society, drinking alcohol, bullying and so on. The application of an innovative curriculum in realizing character competencies in the digital era is very much needed. The independent curriculum is an innovative curriculum in the modern era. Character education in the independent curriculum is very important because it has several main objectives. First, character education aims to develop the basic character of students who adhere to the principles of Pancasila values, such as religiousness, nationalism, integrity, independence and mutual cooperation. Second, the character of education is expected to form students who have religious spiritual strength, self-control, personality, intelligence, noble morals, and other skills needed to face complex future challenges. The method in this research uses library research. Through the new policy for reforming the quality of education in Indonesia, the "Freedom of Learning" curriculum and character education, it is hoped that there will be significant movement in the learning process to improve the quality of education and improve the quality of students in the digital era.